2023
DOI: 10.1186/s40168-023-01469-2
|View full text |Cite
|
Sign up to set email alerts
|

The diet rapidly and differentially affects the gut microbiota and host lipid mediators in a healthy population

Abstract: Background Bioactive lipids produced by human cells or by the gut microbiota might play an important role in health and disease. Dietary intakes are key determinants of the gut microbiota, its production of short-chain (SCFAs) and branched-chain fatty acids (BCFAs), and of the host endocannabinoidome signalling, which are all involved in metabolic diseases. This hypothesis-driven longitudinal fixed sequence nutritional study, realized in healthy participants, was designed to determine if a lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
4

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 74 publications
1
41
0
4
Order By: Relevance
“…Dietary interventions inevitably influence the composition of the gut microbiota, which plays a pivotal role in nutrient digestion and absorption, often determining the effectiveness of dietary outcomes. , To investigate the impact of QJS on the gut microbiota, we conducted 16s rDNA sequencing on fecal samples from different groups. Our findings revealed that the Pac group exhibited a higher Firmicutes to Bacteroidetes (F/B) ratio (1.05 ± 0.92) compared to the tumor model group (0.72 ± 0.94) (Figure a), indicating dysbiosis in the paclitaxel-treated tumor-bearing mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary interventions inevitably influence the composition of the gut microbiota, which plays a pivotal role in nutrient digestion and absorption, often determining the effectiveness of dietary outcomes. , To investigate the impact of QJS on the gut microbiota, we conducted 16s rDNA sequencing on fecal samples from different groups. Our findings revealed that the Pac group exhibited a higher Firmicutes to Bacteroidetes (F/B) ratio (1.05 ± 0.92) compared to the tumor model group (0.72 ± 0.94) (Figure a), indicating dysbiosis in the paclitaxel-treated tumor-bearing mice.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, our study not only provides novel insights into the impact of an amino acid-balanced supplement guided by ExAAs on the transcriptome profiles of skeletal muscle in a breast tumor mouse model but also reveals the intricate interplay between nutritional intervention, immune responses, and muscle strength alteration. The distinct transcriptome signatures, the enrichment of complement-related pathways, and the alterations in specific genes and immune cell populations collectively shed light on the potential mechanism underlying the observed muscle strength enhancement in 29,30 To investigate the impact of QJS on the gut microbiota, we conducted 16s rDNA sequencing on fecal samples from different groups. Our findings revealed that the Pac group exhibited a higher Firmicutes to Bacteroidetes (F/B) ratio (1.05 ± 0.92) compared to the tumor model group (0.72 ± 0.94) (Figure 6a), indicating dysbiosis in the paclitaxel-treated tumor-bearing mice.…”
Section: Transcriptomic Impact Of An Amino Acid Balanced Supplement O...mentioning
confidence: 99%
“…These findings align with previous research demonstrating a reproducible increase in these genera through an MD. 72 A growing body of evidence underscores the pivotal role of Akkermansia muciniphila , a mucin-degrading bacterium, in influencing the host brain function via the gut-brain axis. Studies actively investigating its potential role in AD have proposed several plausible mechanisms, including regulation and protection of the integrity of the intestinal mucosal barrier and modulation of immune responses and metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Liang et al (2017) found that in patients with CRC and adenoma, the organization of the intestinal microbiota is disturbed, which is not the case in healthy patients. Switching from an African-derived diet (high in plant polysaccharides including fibre, and low in fat and processed meat) to a typical Western diet (low in plant polysaccharides/fiber and high in fat, processed meat, and sugar) has been found to lead to a rapid change in the composition and population density of the intestinal microbiota [65][66]. After the absorption of nutrients in the small intestine, waste products, which are basically complex carbohydrates (dietary fibre), protein residues and primary bile acids, secreted by the liver to digest fats, arrive in the colon.…”
Section: Diet Intestinal Microbiota and Colorectal Cancermentioning
confidence: 99%